The Art of Writing an Effective Grant Proposal - Hidayat, Mariyah (Journal of University College of Medicine and Dentistry, 2022)
Writing an effective grant proposal is one of the most important skills in ensuring a successful career in academia. To acquire funding for research activities, increase visibility of oneself or ones’ organization or to facilitate in preparing and launching a product, grant writing has become an essential activity. The art of convincing funding bodies through persuasive and compelling proposals is all the more important for early-stage researchers willing to progress in their career.